1997
DOI: 10.1128/iai.65.3.877-881.1997
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal production of interleukin-12 and gamma interferon in patients with bacterial meningitis

Abstract: To assess the role of interleukin-12 (IL-12) and gamma interferon (IFN-␥) in children with bacterial meningitis, bioactive IL-12 (p70) and the inactive subunit p40 and IFN-␥ were measured in serum and cerebrospinal fluid (CSF) from 35 children with bacterial meningitis and 10 control subjects. The production of IFN-␥ is induced by IL-12 with tumor necrosis factor alpha (TNF-␣) as a costimulator and inhibited by IL-10. CSF concentrations of IL-12 p40 as well as those of IFN-␥ were markedly elevated, whereas IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(16 citation statements)
references
References 31 publications
2
12
0
1
Order By: Relevance
“…5 are not only in accordance with previous results, but also might give new approach to the mechanisms of adjuvancy of VA-MENGOC-BC 0 . Further studies would be required, but absence of correlation observed years ago between serum antibodies and protective e¤cacy [21], might be explained by more recent ¢nding [22] which, in agreement with our present study, might suggest a concomitant and perhaps more appropriate development of a TH1 immune response.…”
Section: Discussionsupporting
confidence: 86%
“…5 are not only in accordance with previous results, but also might give new approach to the mechanisms of adjuvancy of VA-MENGOC-BC 0 . Further studies would be required, but absence of correlation observed years ago between serum antibodies and protective e¤cacy [21], might be explained by more recent ¢nding [22] which, in agreement with our present study, might suggest a concomitant and perhaps more appropriate development of a TH1 immune response.…”
Section: Discussionsupporting
confidence: 86%
“…In BM patients, we observed a positive correlation between IDO activity and the inflammatory cytokines IFN-γ and IL-1Ra (Table 2 ). Although each cytokine displays different roles in the inflammation during BM, IFN-γ seems to have a crucial role, mainly during pneumococcal meningitis [ 32 - 35 ], showing to be involved in deleterious proinflammatory effects [ 34 , 35 ]. Concomitantly, KYN metabolites showed a positive correlation with TNF-α and KYNA metabolites with IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions almost no endogenous interferon‐γ is detectable in the CNS. In case of CNS inflammation, secretion of interferon‐γ, mainly by infiltrating leukocytes, leads to increased CNS concentrations of this cytokine (Kornelisse et al. 1997).…”
Section: Methodsmentioning
confidence: 99%